ISLAM AS AN IDEAL MODERN SOCIAL SYSTEM (A Study of Ali Shariati’s Thought) - Rahman, M. Taufiq (Universitas Islam Negeri Sunan Gunung Djati Bandung, 2016)
This article reexamines Ali Shariati’s thought in formatting Islamic social order. The discussion is important in lighting discourses on Islamic society which is now being evaporated but has new challenges in new circumstances and time of the Muslim community. By taking the texts translated from Shariati’s books and articles this study describes and analyzes the format of Shariati’s thought, what are being rejected by him, and what is the formulation being proposed by him in order to develop Islamic community. Finally, it also contextualizes Shariati’s thought with what being happened in its time in direction to project to our time.